If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(5n + 4) = 8(1 + 2n) Reorder the terms: 8(4 + 5n) = 8(1 + 2n) (4 * 8 + 5n * 8) = 8(1 + 2n) (32 + 40n) = 8(1 + 2n) 32 + 40n = (1 * 8 + 2n * 8) 32 + 40n = (8 + 16n) Solving 32 + 40n = 8 + 16n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-16n' to each side of the equation. 32 + 40n + -16n = 8 + 16n + -16n Combine like terms: 40n + -16n = 24n 32 + 24n = 8 + 16n + -16n Combine like terms: 16n + -16n = 0 32 + 24n = 8 + 0 32 + 24n = 8 Add '-32' to each side of the equation. 32 + -32 + 24n = 8 + -32 Combine like terms: 32 + -32 = 0 0 + 24n = 8 + -32 24n = 8 + -32 Combine like terms: 8 + -32 = -24 24n = -24 Divide each side by '24'. n = -1 Simplifying n = -1
| 7n+15n=176 | | 3x+x+(x-2)=110 | | 4x^2-18x-6=0 | | 4x+6=39-7x | | x/10=-29 | | (7a-b)(7a+b)= | | -5+2x=2x+19 | | 2x+8y=110 | | 2/7(14a+7/2)-3a=9 | | 2-(2x-5)=(x-4) | | -a-12=-4 | | 4x+(x-2)=110 | | -4x-18=30 | | 3x+9=-19+4x | | 6(2x-5)=(x-4) | | -6sin(9t)+3cos(9t)=0 | | -sin(9t)+3cos(9t)=0 | | 9x-1+4x=8x-7 | | 10-5(x-1)=5-x | | 2(3r+5)=-5(-4-2r)-6r | | P^2-2p-15= | | 0.5(k-5)=3 | | 6(1-n)=6n+1 | | 7x+1=2x-29 | | x*5+x=90 | | 2+6x=5x+7 | | 6x+6+4x=16 | | X+2=52-4x | | 2n^2+6n+8=0 | | 3x+12+2x+13=180 | | (7a-2)-(-3a+1)=-3(1-3a) | | z^2=-144 |